Molded product, manufacturing method for molded product, and article

By forming a polymer layer containing specific monomers on the surface of the substrate, the problem of easy peeling of polymer-rich brushes during friction is solved, and a polymer layer with high wear resistance and low friction is achieved, which improves the durability and service life of the material.

JP7626397B2Active Publication Date: 2025-02-04DAINICHISEIKA COLOR & CHEMICALS MFG CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021156932
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-09-27
Publication Date
2025-02-04
Estimated Expiration
2041-09-27

AI Technical Summary

Technical Problem

In the prior art, polymer-rich brushes are easily peeled off by solvent or separated from the substrate during friction, and the process of introducing polymer starting groups is complicated, resulting in insufficient durability and wear resistance.

Method used

A polymer layer containing plastic alcohol units, aromatic vinyl monomers, (meth)acrylate monomers and (meth)acrylamide monomers is used to form a polymer (II) layer through active radical polymerization, controlling its average molecular weight and molecular weight distribution to ensure a high occupancy and thickness of the polymer layer on the surface of the substrate.

Benefits of technology

The high thickness and wear resistance of the polymer layer are achieved, making it difficult to separate from the substrate, providing excellent durability and low friction characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007626397000015
    Figure 0007626397000015
  • Figure 0007626397000016
    Figure 0007626397000016
  • Figure 0007626397000001
    Figure 0007626397000001
Patent Text Reader

Abstract

To provide a molding comprising a polymer layer, having sufficient thickness, resistance to detachment, and excellent durability such as wear resistance.SOLUTION: A molding comprises a substrate comprising a polymer (i) having a vinyl alcohol unit, and a polymer (ii) layer that is provided on the substrate and has a constitutional unit derived from monomers such as an aromatic vinyl monomer. The polymers (i) and (ii) are bound with the following structure of formula (1). The polymer (ii) layer has a thickness of 0.1-5 μm. The areal percentage σ* of the polymer (ii) on the substrate surface has 0.1 or more. (R1 is H, a methyl group, an ethyl group, a phenyl group, or an acyl group, R 2 is a methyl group, an ethyl group, or an acyl group, Polymer (i) is the polymer (i), and Polymer (ii) is the polymer (ii)).SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a molded product, a method for producing a molded product, and an article. [Background technology]

[0002] As a method for modifying a substrate, a method is known in which a polymer having a group at its end capable of adsorbing or reacting with the substrate is applied to the substrate to form a physically or chemically bonded polymer layer on the substrate surface. Also known is a method in which a polymerizable group provided on the substrate surface is used as a starting point to polymerize a monomer to form a grafted polymer layer from the substrate surface.

[0003] In recent years, so-called "concentrated polymer brushes" have been studied, which are densely grafted onto a substrate using the technology of living radical polymerization developed in the 1990s. In these concentrated polymer brushes, polymer chains are grafted onto a substrate at high density (surface occupancy (σ*) 0.1 or more) with intervals of 1 to 4 nm. Such concentrated polymer brushes can modify the substrate surface and impart characteristics such as low friction, suppression of protein adsorption, size exclusion properties, hydrophilicity, water repellency, etc. (Patent Documents 1 and 2, Non-Patent Documents 1 to 3). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2008-133434 A [Patent Document 2] JP 2010-261001 A [Non-patent literature]

[0005] [Non-Patent Document 1] Adv. Polym. Sci., 2006, 197, 1-45 [Non-Patent Document 2] J.Am.Chem.Soc.,2005,127,15843-15847 [Non-Patent Document 3] Polym. Chem., 2012, 3, 148-153 Summary of the Invention [Problem to be solved by the invention]

[0006] Concentrated polymer brushes (hereinafter simply referred to as "brushes") exhibit low friction in the tribology fields of lubrication, friction, and wear. However, the lubricating oil or solvent used during friction can cause the polymer layer of the brush to easily detach from the substrate surface. Concentrated polymer brushes are formed by forming a polymerization initiation base layer, which is a monolayer, followed by polymerization. However, because the bonding strength and adhesion of the monolayer are weak, it is thought that the polymer layer is easily detached by friction or solvents.

[0007] Concentrated polymer brushes are formed, for example, by living radical polymerization using a substrate to which a polymerization initiator group has been added. However, as mentioned above, the binding strength of the polymerization initiator group to the substrate surface is weak, and the group may be easily detached. In addition, the process of adding (introducing) the polymerization initiator group to the substrate surface is often complicated, leaving room for improvement.

[0008] The present invention has been made in consideration of the problems of the conventional techniques, and an object of the present invention is to provide a molded article having a polymer layer that has a sufficient thickness, is not easily detached, and has excellent durability such as abrasion resistance, etc. Another object of the present invention is to provide a method for producing the molded article, and an article including the molded article. [Means for solving the problem]

[0009] That is, according to the present invention, there is provided the following molded article. [1] A molded article comprising: a substrate containing a polymer (i) having a vinyl alcohol unit; and a polymer (ii) layer provided on a surface of the substrate, the polymer (i) containing a polymer (ii) having a structural unit derived from at least one monomer selected from the group consisting of an aromatic vinyl monomer, a (meth)acrylate monomer, and a (meth)acrylamide monomer, wherein the polymer (i) and the polymer (ii) are bonded together in a structure represented by the following general formula (1), the number average molecular weight of the polymer (ii) is 500,000 to 5,000,000 and the molecular weight distribution (weight average molecular weight / number average molecular weight) is less than 1.5, the thickness of the polymer (ii) layer is 0.1 to 5 μm, and the occupancy rate σ* of the polymer (ii) on the surface of the substrate is 0.1 or more.

[0010] TIFF0007626397000001.tif36170 (In the general formula (1), R1 represents a hydrogen atom, a methyl group, an ethyl group, a phenyl group, or an acyl group; R2 represents a methyl group, an ethyl group, or an acyl group; "Polymer(i)" represents polymer (i); and "Polymer(ii)" represents polymer (ii).

[0011] [2] The molded article according to [1], wherein the polymer (ii) layer is swollen with a solvent.

[0012] According to the present invention, there is also provided a method for producing a molded article as described below. [3] A method for producing a molded product according to the above [1] or [2], comprising the steps of reacting a compound represented by the following general formula (2) with a surface of a substrate containing a polymer (i) having a vinyl alcohol unit, thereby introducing a functional group represented by the following general formula (3) onto the surface of the substrate, and polymerizing at least one monomer selected from the group consisting of an aromatic vinyl monomer, a (meth)acrylate monomer, and a (meth)acrylamide monomer under a pressure condition of 10 to 1,000 MPa to form a polymer (ii), and providing a polymer (ii) layer containing the polymer (ii) on the surface of the substrate.

[0013] TIFF0007626397000002.tif30170 (In the general formula (2), R1 represents a hydrogen atom, a methyl group, an ethyl group, a phenyl group, or an acyl group; R2 represents a methyl group, an ethyl group, or an acyl group; X represents a chlorine atom, a bromine atom, or an iodine atom; and Y represents a chlorine atom, a bromine atom, or a hydroxyl group.)

[0014] TIFF0007626397000003.tif28170 (In the general formula (3), R1 represents a hydrogen atom, a methyl group, an ethyl group, a phenyl group, or an acyl group; R2 represents a methyl group, an ethyl group, or an acyl group; X represents a chlorine atom, a bromine atom, or an iodine atom; and "*" represents the bonding position with the polymer (i))

[0015] [4] The method for producing a molded article according to [3] above, wherein the polymer (ii) is formed by surface-initiated living radical polymerization of the monomer. [5] The method for producing a molded article according to the above [3] or [4], wherein the monomer is polymerized in an ionic liquid to form the polymer (ii). [6] The method for producing a molded article according to any one of the above [3] to [5], wherein the compound represented by the general formula (2) is 2-bromo-2-methylpropionic acid bromide.

[0016] Furthermore, according to the present invention, there are provided the following articles: [7] An article comprising the molded article described in [1] or [2] above. Effect of the Invention

[0017] According to the present invention, it is possible to provide a molded article including a polymer layer that has a sufficient thickness, is not easily detached, and has excellent durability such as abrasion resistance. Furthermore, according to the present invention, it is possible to provide a method for producing the above molded article, and an article including the above molded article. [Brief description of the drawings]

[0018] [Figure 1]1 shows the results of infrared absorption spectrum measurement (IR chart) of the PET film and the polymer (ii) layer constituting the molded product-7 obtained in Example 7. [Diagram 2] 1 is an electron microscope photograph showing the cross-sectional microstructure of Molded Product-7 obtained in Example 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] <Molded object> Hereinafter, the embodiment of the present invention will be described, but the present invention is not limited to the following embodiment. The molded product of the present invention comprises a substrate containing a polymer (i) having a vinyl alcohol unit, and a polymer (ii) layer provided on the surface of the substrate, the polymer (ii) containing a structural unit derived from at least one monomer selected from the group consisting of an aromatic vinyl monomer, a (meth)acrylate monomer, and a (meth)acrylamide monomer. The polymer (i) and the polymer (ii) are bonded to each other in a structure represented by the following general formula (1). The number average molecular weight of the polymer (ii) is 500,000 to 5,000,000, and the molecular weight distribution (weight average molecular weight / number average molecular weight) is less than 1.5. The thickness of the polymer (ii) layer is 0.1 to 5 μm, and the occupancy rate σ* of the polymer (ii) on the surface of the substrate is 0.1 or more. Hereinafter, the molded product of the present invention will be described in detail.

[0020] TIFF0007626397000004.tif36170 (In the general formula (1), R1 represents a hydrogen atom, a methyl group, an ethyl group, a phenyl group, or an acyl group; R2 represents a methyl group, an ethyl group, or an acyl group; "Polymer(i)" represents polymer (i); and "Polymer(ii)" represents polymer (ii).)

[0021] (base material) The substrate is composed of a polymer (i) having a vinyl alcohol unit, and is preferably substantially formed of the polymer (i). That is, at least the surface has a hydroxyl group. By utilizing this hydroxyl group, a functional group that functions as a polymerization initiating group can be easily introduced to the surface of the substrate. Then, by forming the polymer (ii) in a brush shape from the introduced polymerization initiating group, a molded article having a polymer (ii) layer containing the polymer (ii) can be obtained. Since the substrate itself has a hydroxyl group, even if a brush-shaped polymer (ii) is formed from the added polymerization initiating group, the polymerization initiating group and the polymer (ii) are not substantially detached, and the durability of the polymer (ii) layer is improved.

[0022] Examples of the polymer (i) having a vinyl alcohol unit include polyvinyl alcohol, polyethylene vinyl alcohol, polyvinyl butyral, polyvinyl formal, polyvinyl alcohol-poly(meth)acrylic acid copolymer, polyvinyl alcohol-poly(meth)acrylate copolymer, polyvinyl alcohol-vinyl chloride copolymer, polyvinyl alcohol-vinylidene chloride copolymer, polyvinyl acetate polyvinyl alcohol, polyvinyl chloride-polyvinyl acetate-polyvinyl alcohol copolymer, polyvinyl chloride-polyvinylidene chloride-polyvinyl alcohol copolymer, butenediol-vinyl alcohol copolymer, crosslinked structures utilizing the hydroxyl groups of these, block copolymers, and graft copolymers.

[0023] Among them, the polymer (i) is preferably a crosslinked structure of polyvinyl alcohol capable of imparting hydroxyl groups to the surface of a material such as a film by coating or the like, or a polyethylene vinyl alcohol having hydroxyl groups on its surface, which is used for films, containers, etc. Examples of the crosslinked structure of polyvinyl alcohol include crosslinked structures of polyvinyl alcohol crosslinked with boric acid, polycarboxylic acid, polyisocyanate, polyaldehyde compound, etc.

[0024] Examples of the shape of the substrate include molded products such as films, sheets, disks, sponges, lenses, tubes, pipes, sticks, fibers, nonwoven fabrics, and bottles. The substrate may be used as is, or may be surface-treated to activate the surface. Examples of the surface treatment include plasma treatment, ultraviolet irradiation treatment, ozone oxidation treatment, radiation treatment, X-ray treatment, electron beam treatment, laser treatment, and surface treatment with functional groups.

[0025] The substrate may be a material formed by applying polymer (i) to the surface of other polymers such as polyethylene terephthalate, polycarbonate, polyolefin, polystyrene, polyamide, engineering plastics, etc.; silicon compounds such as glass and silicon; metals such as aluminum and stainless steel; ceramics such as alumina, silicon carbide, silicon nitride, etc. Also, a molded product such as a film, sheet, or part to which a coating film of a crosslinked structure crosslinked with a crosslinking agent is applied may also be used as the substrate. Examples of methods for applying polymer (i) to the surface of various materials include screen printing, dip coating, inkjet printing, spin coating, blade coating, bar coating, slit coating, edge casting, spray coating, roll coating, curtain coating, gravure printing, flexographic printing, and gravure offset printing.

[0026] (Polymer (ii) Layer) The polymer (ii) layer is a layer that is provided on the surface of the substrate and that contains the polymer (ii), and is preferably a layer that is substantially formed of the polymer (ii). The polymer (ii) has a constituent unit derived from at least one monomer selected from the group consisting of an aromatic vinyl monomer, a (meth)acrylate monomer, and a (meth)acrylamide monomer. As a monomer that constitutes the polymer (ii), a (meth)acrylate monomer is preferred because it has a high polymerization rate and the polymerization conditions are mild. Among them, a methacrylate monomer is preferred because it has good living properties and can form a polymer (ii) with a higher molecular weight.

[0027] Examples of the aromatic vinyl monomer include styrene, vinyl toluene, vinyl hydroxybenzene, chloromethyl styrene, vinyl naphthalene, vinyl biphenyl, vinyl ethyl benzene, vinyl dimethyl benzene, and α-methyl styrene.

[0028] Examples of (meth)acrylate monomers include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, 2-methylpropane (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, tetradecyl (meth)acrylate, octadecyl (meth)acrylate, behenyl (meth)acrylate, and isostearyl (meth)acrylate. Examples of the aliphatic, alicyclic, aromatic alkyl, and halogenated alkyl (meth)acrylates include cyclohexyl (meth)acrylate, t-butylcyclohexylmethyl (meth)acrylate, isobornyl (meth)acrylate, trimethylcyclohexyl (meth)acrylate, cyclodecyl (meth)acrylate, cyclodecylmethyl (meth)acrylate, benzyl (meth)acrylate, t-butylbenzotriazolephenylethyl (meth)acrylate, phenyl (meth)acrylate, naphthyl (meth)acrylate, allyl (meth)acrylate, trifluoroethyl (meth)acrylate, perfluoropentyl (meth)acrylate, and perfluorooctyl (meth)acrylate. The (meth)acrylate monomer may contain a hydroxyl group, a glycol group, an acid group (such as a carboxyl group, a sulfonic acid group, or a phosphoric acid group), an oxygen atom, an amino group, a nitrogen atom, or a silicon atom.

[0029] Examples of the (meth)acrylamide monomer include (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-hydroxyethyl(meth)acrylamide, and (meth)acryloylmorpholine.

[0030] By selecting and using a monomer, a polymer (ii) layer having a function according to the characteristics of the polymer (ii) to be formed can be formed. For example, by using a fluorine-based monomer, a polymer (ii) layer that easily repels water and oil and has low surface tension can be formed. In addition, by using a monomer having a polyethylene glycol group or a carboxy group, a hydrophilic polymer (ii) layer having properties such as anti-fogging can be formed. Furthermore, a biocompatible polymer (ii) layer to which proteins and the like do not easily adhere can be formed. Then, it can be swollen with a lubricating oil or the like to form a lubricating film, and a polymer (ii) layer with extremely low friction can be formed.

[0031] The polymer (i) constituting the substrate and the polymer (ii) constituting the polymer (ii) layer are bonded through a structure represented by the following general formula (1).

[0032] TIFF0007626397000005.tif36170 (In the general formula (1), R1 represents a hydrogen atom, a methyl group, an ethyl group, a phenyl group, or an acyl group; R2 represents a methyl group, an ethyl group, or an acyl group; "Polymer(i)" represents polymer (i); and "Polymer(ii)" represents polymer (ii).

[0033] Examples of the structure represented by general formula (1) (the structure of the portion excluding "Polymer (i)" and "Polymer (ii)") include an ethylenecarbonyloxy group, a 1-propylenecarbonyloxy group, an acetylmethylenecarbonyloxy group, a 2-propylenecarbonyloxy group, a 2-butylenecarbonyloxy group, a 1-phenyl-1-ethylenecarbonyloxy group, and a 1-phenyl-1-propylenecarbonyloxy group. Among these, a 2-propylenecarbonyloxy group derived from 2-bromoisobutyric acid bromide, which is a compound capable of introducing a polymerization initiator group having a good initiation efficiency under mild living radical polymerization conditions, is preferred.

[0034] The number average molecular weight (Mn) of the polymer (ii) is 500,000 to 5 million, preferably 700,000 to 4 million, more preferably 1 million to 3 million. If the Mn of the polymer (ii) is less than 500,000, the thickness of the polymer (ii) layer is insufficient. On the other hand, it is difficult to polymerize a polymer (ii) having an Mn of more than 5 million, and the molecular weight distribution (PDI) may become excessively large due to the large number of termination reactions in side reactions. In this specification, the Mn and Mw of the polymer (ii) are values ​​calculated in terms of polystyrene measured by gel permeation chromatography (GC).

[0035] The molecular weight distribution (PDI = weight average molecular weight (Mw) / number average molecular weight (Mn)) of polymer (ii) is less than 1.5, preferably 1.4 or less, and more preferably 1.3 or less. PDI is a physical property that serves as an index of the variation in the molecular weight of a polymer. If the PDI is 1.5 or more, the variation in molecular weight is large, so that molecular chains with large molecular weight (long) tend to protrude from the surface of the formed polymer (ii) layer, which may impair the characteristics of a concentrated polymer brush.

[0036] The thickness of the polymer (ii) layer is 0.1 to 5 μm, preferably 0.2 to 3 μm, and more preferably 0.5 to 1.5 μm. By setting the thickness of the polymer (ii) within the above range (i.e., high film thickness), durability such as abrasion resistance can be improved. If the thickness of the polymer (ii) layer is less than 0.1 μm, the abrasion resistance is insufficient. On the other hand, if the thickness of the polymer (ii) layer is more than 5 μm, the polymerization time of the polymer (ii) becomes excessively long, and it is substantially difficult to produce a high molecular weight polymer (ii) to achieve that thickness.

[0037] The occupancy rate (surface occupancy rate σ*) of the polymer (ii) on the surface of the substrate is 0.1 or more, preferably 0.1 to 1.0, more preferably 0.15 to 0.8, and particularly preferably 0.2 to 0.7. By setting the surface occupancy rate σ* of the polymer (ii) within the above range, the characteristics as a concentrated polymer brush can be exhibited. That is, by forming a polymer (ii) layer by the polymer (ii) which is a concentrated polymer brush, an effective brush effect is exhibited, and it becomes possible to use it in various applications. And, by reducing frictional energy loss and preventing wear due to the extremely low friction, it is possible to impart effects such as long life, antibacterial and antiviral properties due to size exclusion properties, antifouling resistance, and protein adhesion prevention properties, and effects such as high lubricity and high slipperiness due to liquid retention properties to the molded product.

[0038] The surface occupancy rate σ* is calculated by the following formula (A) 2 )" according to the following formula (B). σ = dLNAMn (A) d: density of polymer (polymer (ii)) L: thickness of polymer layer (polymer (ii) layer) NA: Avogadro's number Mn: number average molecular weight of polymer (polymer (ii)) σ*=a 2 σ (B) a 2 : Monomer cross-sectional area

[0039] The thickness of the polymer (ii) layer can be measured according to a conventionally known method using, for example, an ellipsometer, an electron microscope, an atomic force microscope, etc. The density of the polymer (ii) can be a value described in a conventionally known document or a value measured according to a method described in JIS K 7112:1999, etc.

[0040] The variation in thickness of the polymer (ii) layer is preferably within ±20%, more preferably within ±10%, based on the average thickness of the polymer (ii) layer. The average thickness of the polymer (ii) layer is the average value of the thicknesses of the polymer (ii) layer measured at any 10 points. If the variation in thickness of the polymer (ii) layer exceeds ±20%, the smoothness of the polymer (ii) layer may be slightly reduced, and the brush effect may be insufficient.

[0041] The polymer (ii) layer is preferably swollen with a solvent, since this will provide a more effective brush effect. As a solvent for swelling the polymer (ii) layer, it is preferable to use a liquid medium that has affinity for dissolving the polymer (ii). By swelling the polymer (ii) layer with such a liquid medium, the thickness of the polymer (ii) layer can be increased by 1.1 to 3 times.

[0042] Examples of the solvent (liquid medium) for swelling the polymer (ii) layer include water-based lubricants and lubricating oils. Examples of the water-based lubricants include water, glycerin, polyethylene glycol, and polypropylene glycol. Examples of the lubricating oil include hydrocarbon-based lubricating oils, ester-based lubricating oils, silicone oils, and ionic liquids. By swelling the polymer (ii) layer with these liquid media, the brush effect of extremely low friction, size exclusion properties, high liquid retention, and the like can be effectively exerted. This makes it possible to provide various articles that are endowed with properties such as energy saving, long life, and high performance.

[0043] The polymer (ii) layer may be provided on the entire surface of the substrate, or may be provided on a part of the surface of the substrate. The surface of the substrate on which the polymer (ii) layer is not provided may be subjected to other surface treatments or coatings. For example, by providing a polymer (ii) layer on one side of a film-like substrate and providing an adhesive layer or an adhesive layer on the other side, a molded product that can be attached to various articles and the like can be obtained.

[0044] <Method of manufacturing molded products> The molded article of the present invention can be produced by the method shown below. That is, the method for producing the molded article of the present invention includes a step (step (1)) of reacting a compound represented by the following general formula (2) with the surface of a substrate containing a polymer (i) having a vinyl alcohol unit to introduce a functional group represented by the following general formula (3) onto the surface of the substrate, and a step (step (2)) of polymerizing at least one monomer selected from the group consisting of an aromatic vinyl monomer, a (meth)acrylate monomer, and a (meth)acrylamide monomer to form a polymer (ii), and providing a polymer (ii) layer containing the polymer (ii) on the surface of the substrate.

[0045] TIFF0007626397000006.tif30170 (In the general formula (2), R1 represents a hydrogen atom, a methyl group, an ethyl group, a phenyl group, or an acyl group; R2 represents a methyl group, an ethyl group, or an acyl group; X represents a chlorine atom, a bromine atom, or an iodine atom; and Y represents a chlorine atom, a bromine atom, or a hydroxyl group.)

[0046] TIFF0007626397000007.tif28170 (In the general formula (3), R1 represents a hydrogen atom, a methyl group, an ethyl group, a phenyl group, or an acyl group; R2 represents a methyl group, an ethyl group, or an acyl group; X represents a chlorine atom, a bromine atom, or an iodine atom; and "*" represents the bonding position with the polymer (i))

[0047] (Process (1)) In step (1), a compound represented by general formula (2) is reacted with the surface of the substrate to introduce a functional group represented by general formula (3) onto the surface of the substrate. Hydroxyl groups are present on the surface of the substrate formed of polymer (i). Therefore, by reacting the compound represented by general formula (2), a functional group (polymerization initiating group) represented by general formula (3) can be introduced onto the surface of the substrate.

[0048] Examples of the compound represented by the general formula (2) include compounds having a carboxy group such as 2-chloropropionic acid, 2-bromopropionic acid, 2-iodopropionic acid, 2-chloro-2-methylpropionic acid, 2-bromo-2-methylpropionic acid, 2-iodo-2-methylpropionic acid, 3-chloro-3-methylbutanoic acid, 3-bromo-3-methylbutanoic acid, 2-bromo-2-phenylpropionic acid, and 2-acetyl-2-bromopropionic acid; 2-chloropropionic acid chloride, 2-bromopropionic acid, and the like. Examples of the acid halide include acid halide such as 2-bromopropionic acid bromide, 2-iodopropionic acid chloride, 2-chloro-2-methylpropionic acid chloride, 2-bromo-2-methylpropionic acid bromide, 2-iodo-2-methylpropionic acid bromide, 3-chloro-3-methylbutanoic acid chloride, 3-bromo-3-methylbutanoic acid bromide, 2-bromo-2-phenylpropionic acid bromide, and 2-acetyl-2-bromopropionic acid bromide. Among them, 2-bromo-2-methylpropionic acid bromide is preferred. 2-bromo-2-methylpropionic acid bromide is an easily available compound, and the halogen atom is easily eliminated, and the radical generated on the quaternary carbon is relatively stable, so that side reactions can be suppressed. In addition, the reaction proceeds quickly at low temperatures, making it easy to produce molded products.

[0049] Specific methods for introducing a polymerization initiator group by reacting a compound having a carboxyl group with the surface of a substrate include a method of dehydrating by heating and esterifying; a method of esterifying using a dehydrating agent such as a carbodiimide compound; a method of esterifying via a carboxylic anhydride using trifluoroacetic anhydride; and the like. Specific methods for introducing a polymerization initiator group by reacting an acid halide with the surface of a substrate include a method of esterifying by reacting in the presence of a base such as an amine, and the like. Among these, it is preferable to use an acid halide, since it can be reacted quickly at a low temperature.

[0050] (Process (2)) In step (2), at least one monomer selected from the group consisting of aromatic vinyl monomers, (meth)acrylate monomers, and (meth)acrylamide monomers is polymerized to form polymer (ii) in the presence of a substrate having a polymerization initiator group (functional group represented by general formula (3)) introduced on its surface. This allows a polymer (ii) layer containing polymer (ii) to be disposed on the surface of the substrate, thereby obtaining the desired molded product.

[0051] The polymerization method includes radical polymerization using a radical generator such as an azo initiator or peroxide. Among them, living radical polymerization is preferred, and surface-initiated living radical polymerization in which polymerization is initiated and progresses from the surface is more preferred. In general formula (3), a halogen atom such as a chlorine atom represented by X is eliminated as a halogen radical by the action of light, heat, radicals, etc., to generate a tertiary or quaternary carbon radical. The generated tertiary or quaternary carbon radical attacks and reacts with a monomer having a radically polymerizable group, and the polymer (ii) is elongated.

[0052] Examples of living radical polymerization include atom transfer radical polymerization (ATRP), iodine transfer radical polymerization (ITP), reversible transfer catalyzed polymerization (RTCP), and reversible coordination mediated polymerization (RCMP). Among them, the ATRP method is preferred. The ATRP method is a living radical polymerization method that utilizes oxidation-reduction using a metal complex as a catalyst. Examples of the metal catalyst include complexes of copper chloride or copper bromide with polyamines such as dinonyl bipyridine, tridimethylaminoethylamine, and pentamethyldiethylenetriamine; and dichlorotris(triphenylphosphine)ruthenium. The ATRP method may be bulk polymerization or solution polymerization using an organic solvent or the like. Examples of the organic solvent that can be used include hydrocarbon solvents, ester solvents, glycol solvents, ether solvents, amide solvents, alcohol solvents, sulfoxide solvents, urea solvents, and ionic liquids. In the ATRP method, in order to enhance the reductivity of the oxidation-reduction, a reducing agent such as tin dilaurate or an azo-based polymerization initiator may be used.

[0053] Since the ATRP method uses heavy metals, it is necessary to consider coloration and environmental load, and it is also necessary to remove heavy metals from the reaction system. For this reason, it is preferable to carry out polymerization in the presence of a general-purpose organic compound that does not use heavy metals. Specifically, it is preferable to carry out surface-initiated radical polymerization or surface-initiated living radical polymerization in the presence of at least one salt selected from the group consisting of quaternary ammonium halide salts, quaternary phosphonium halide salts, and alkali metal halide salts. This allows polymerization to be carried out using commercially available inexpensive organic materials and inorganic salts. In addition, since there is no need to remove metals, it is possible to reduce the load on the environment and simplify the process.

[0054] Examples of the quaternary ammonium halide salt include benzyltrimethylammonium chloride, tetrabutylammonium bromide, tetrabutylammonium iodide, tetraoctylammonium iodide, nonylpyridinium chloride, and choline chloride. Examples of the quaternary phosphonium halide salt include tetraphenylphosphonium chloride, methyltributylphosphonium bromide, and tetrabutylphosphonium iodide. Examples of the alkali metal halide salt include lithium bromide and potassium iodide.

[0055] As the salt, it is preferable to use an iodide salt. By using an iodide salt, living radical polymerization proceeds, and a polymer (ii) having a narrower molecular weight distribution can be formed. In addition, it is preferable to use a salt that can be dissolved in a polymerization solution, such as a quaternary ammonium iodide salt, a quaternary phosphonium iodide salt, and an alkali metal iodide salt, and it is more preferable to use a quaternary ammonium iodide salt. Examples of the quaternary ammonium iodide salt include benzyltetrabutylammonium iodide, tetrabutylammonium iodide, tetraoctylammonium iodide, dodecyltrimethylammonium iodide, octadecyltrimethylammonium iodide, and trioctadecylmethylammonium iodide.

[0056] From the viewpoint of increasing the activity and forming a more concentrated and high molecular weight polymer (ii), the amount of the salt relative to the polymerization initiating group is preferably at least an equimolar amount, more preferably at least 10 times the molar amount, and may be at least 100 times the molar amount.

[0057] In the method using the quaternary salt or halide salt, the polymerization conditions are not particularly limited. The polymerization is carried out under conventionally known conditions. The temperature is preferably 60° C. or higher, and an organic solvent is preferably used as the solvent. As the solvent, it is preferable to use a solvent that dissolves the salt, and a highly polar organic solvent such as an alcohol, glycol, amide, urea, sulfoxide, or ionic liquid is preferable.

[0058] In order to stably form a polymer (ii) having a high molecular weight with a number average molecular weight (Mn) of 500,000 to 5,000,000, it is preferable to extend the polymerization time while suppressing the termination reaction derived from radical polymerization. For this reason, the monomer is polymerized under a pressure (external pressure) condition of 10 to 1,000 MPa, preferably 100 to 400 MPa, to form the polymer (ii). By polymerizing the substrate and the monomer by applying a high pressure to a container containing the substrate, the growth rate can be increased and the termination reaction rate can be decreased. For this reason, it is possible to form the polymer (ii) having the desired Mn and PDI in a shorter time (for example, within 10 hours), and a polymer (ii) layer of the desired thickness can be provided on the surface of the substrate. Note that a special device or reaction bath is required to apply a pressure of more than 1,000 MPa.

[0059] As the polymerization vessel, it is preferable to use a vessel that can be sealed and can withstand high pressure. In addition, since pressure needs to be transmitted to the inside of the vessel, it is preferable to use a vessel having a part that deforms under pressure, such as a soft part or an expandable part made of plastic. Specifically, various vessels such as polyethylene bottles, PET bottles, retort pouches, and blister containers can be used. In addition, a vessel made of a material that is not easily deformed at the temperature during polymerization and has heat resistance is preferable. Furthermore, a vessel made of a material that is not easily damaged by the solvent for polymerization and has properties such as chemical resistance and solvent resistance is preferable. Examples of materials that constitute the polymerization vessel include polyolefin resins, fluorine resins, polyester resins, polyamide resins, and engineering plastics. In addition, it is preferable to prevent gas from entering the polymerization vessel as much as possible during polymerization. For example, it is preferable to charge the polymerization solution to 90% or more of the volume of the polymerization vessel.

[0060] From the viewpoint of increasing the growth reaction of the polymer (ii), it is preferable to polymerize the monomer in the ionic liquid to form the polymer (ii). As the ionic liquid, an organic salt that is solid at room temperature (25°C) can be used. Among them, it is preferable to use an ionic liquid such as a quaternary ammonium salt or a quaternary phosphonium salt, and it is more preferable to use an ionic liquid such as a tetraalkyl quaternary ammonium salt, an imidazolium salt, a pyridinium salt, a quaternary phosphonium salt, or a guanidinium salt.

[0061] It is not easy to verify the molecular weight of the polymer (ii) constituting the formed polymer (ii) layer. Therefore, it is preferable to carry out surface-initiated radical polymerization or surface-initiated living radical polymerization in the coexistence of an initiator monomer having the same initiator group as the polymerization initiator group. This forms a free polymer that is not included in the polymer (ii) layer. Then, by measuring the molecular weight of the formed free polymer according to a standard method, the molecular weight of the polymer (ii) constituting the polymer (ii) layer can be estimated. The number average molecular weight (Mn) of the formed free polymer measured by GPC in terms of polystyrene is 500,000 to 5,000,000, and the molecular weight distribution (PDI = weight average molecular weight (Mw) / number average molecular weight (Mn)) is less than 1.5.

[0062] As the initiator monomer, a compound having the same group as the polymerization initiation group is used. Specifically, the compounds represented by the following formulae (4) to (6) can be used as the initiator monomer.

[0063] TIFF0007626397000008.tif37170

[0064] <Goods> The article of the present invention comprises the above-mentioned molded article. As described above, the molded article comprises a polymer (ii) layer, which is a concentrated polymer brush having sufficient thickness, resistance to detachment, and excellent durability such as abrasion resistance. For this reason, the article of the present invention comprising the molded article is suitable for use as, for example, medical equipment, robots, manufacturing equipment, structures, home appliances, vehicles, aircraft, space-related products, containers, packages, electronic devices, battery materials, display materials, and the like. Furthermore, by using a molded article having a polymer (ii) layer swollen with the above-mentioned solvent (liquid medium), various articles having properties such as energy saving, long life, and high performance can be provided. EXAMPLES

[0065] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the examples and comparative examples, "parts" and "%" are by mass unless otherwise specified.

[0066] <Production of Molded Products> Example 1 A polyvinyl alcohol sheet (trade name "Bellclean", manufactured by AION, 30 mm x 50 mm, thickness 1 mm) (PVA sheet) washed with methyl ethyl ketone (MEK), tetrahydrofuran (THF), and isopropyl alcohol (IPA) was prepared as a substrate. 85.5 parts of toluene, 4.5 parts of pyridine, and 10.0 parts of 2-bromo-2-methylpropionic acid bromide (BBiB) were placed in a glass beaker to prepare a solution. A PVA sheet was placed in the beaker and immersed in the solution, and left at room temperature for 1 hour to introduce the 2-bromo-2-methylpropyloxy group, which is a polymerization initiator group, onto the surface of the PVA sheet. The sheet was washed with toluene and methanol and dried to obtain initiator group-imparted substrate-1. ATR-IR was used to measure a 1,735 cm 2 peak derived from the ester bond of the polymerization initiator group. -1 It was observed that the absorption was near

[0067] Under an argon atmosphere, 0.0005 parts of ethyl 2-bromo-2-methylpropionate (EBiB), 0.043 parts of copper (II) bromide (CuBr2), 0.2610 parts of copper (I) bromide (CuBr), 1.7478 parts of 4,4'-dinonyl-2,2'-bipyridyl (dNbpy), 54.06 parts of methyl methacrylate (MMA), and 56.11 parts of anisole were placed in a glass screw tube and stirred to prepare a polymerization solution. The initiator group-imparted substrate-1 and the polymerization solution were placed in an aluminum laminate bag and heat-sealed while removing the gas. The aluminum laminate bag was placed in a high-pressure device (trade name "PV-400", manufactured by Shin Corporation) containing water as a pressure medium, and polymerization was performed for 4 hours at 60 ° C. and 400 MPa. A highly viscous solution containing the formed polymer (ii) was generated in the high-pressure device after polymerization. A portion of the solution was sampled, and the number average molecular weight (Mn) in terms of polymethyl methacrylate (PMMA) was measured by gel permeation chromatography (GPC) using THF as the developing solvent, and the molecular weight distribution (PDI = Mw / Mn) was calculated. The Mn of the formed polymer (ii) was 1.88 million, and the PDI was 1.28. The contents removed from the container were thoroughly washed with THF to obtain molded product-1 in which a polymer (ii) layer was provided on the surface of the substrate. The thickness of the polymer (ii) layer measured by spectroscopic ellipsometry was 1,410 nm. The graft density σ calculated from the above formula (A) was 0.54. The surface occupancy σ* calculated from the above formula (B) was 0.30.

[0068] (Examples 2 to 4) Molded products-2 to -4 were obtained in the same manner as in Example 1 described above, except that the types of monomers shown in Table 1 were used. The meanings of the abbreviations in Table 1 are as follows. In Example 4, Mn of polymer (ii) calculated as PMMA was measured by GPC using an aqueous lithium chloride solution / acetonitrile as the developing solvent. · LMA: Lauryl methacrylate PEGMA: Polyethylene glycol monomethyl ether methacrylate (molecular weight 400) TFSI: Methacryloyloxyethyl diethylmethylammonium bis(trifluoromethanesulfonyl)imide salt

[0069] TIFF0007626397000009.tif64170

[0070] Example 5 Under an argon atmosphere, 56.11 parts of 1-butyl-3-methylimidazolium tetrafluoroboron (BMIMBF4), 54.06 parts of MMA, 0.0005 parts of EBiB, and 3.30 parts of tetrabutylammonium iodide (TBAI) were placed in a flask and stirred to prepare a polymerization solution. The container containing the initiator-imparted substrate-1 and the polymerization solution was placed in an oil bath and polymerized at 80°C and normal pressure for 24 hours. After polymerization, a highly viscous solution containing polymer (ii) was produced in the container. The Mn of the formed polymer (ii) was 510,000 and the PDI was 1.30. The contents removed from the container were thoroughly washed with THF to obtain molded product-5 in which a polymer (ii) layer was provided on the surface of the substrate. The thickness of the polymer (ii) layer was 153 nm, and the surface occupancy σ* was 0.12.

[0071] Example 6 As a substrate, a polyethylene vinyl alcohol film (product name "EVAL EF-E", manufactured by Kuraray Co., Ltd., thickness 30 μm, polyethylene content 44 mol%) was prepared. Initiator group-imparted substrate-2 was obtained in the same manner as in Example 1 described above, except that a polyethylene vinyl alcohol film was used instead of a PVA sheet. Then, molded product-6 was obtained in the same manner as in Example 1 described above, except that initiator group-imparted substrate-2 was used instead of initiator group-imparted substrate-1. The Mn of polymer (ii) was 1.85 million, and the PDI was 1.26. The thickness of the polymer (ii) layer was 1,330 nm, and the surface occupancy σ* was 0.29.

[0072] Example 7 An A4-sized polyethylene terephthalate film (trade name "Lumirror S-10", manufactured by Toray Industries, Inc., thickness 100 μm) (PET film) was prepared. 30.0 parts of a water dispersion (solid content 15%) of polyester (terephthalic acid / isophthalic acid / 5-sodium sulfoisophthalic acid / ethylene glycol / diethylene glycol copolymer = 49 / 18 / 3 / 40 / 60 mass ratio, Mn 20,000, acid value 2 mgKOH / g), 45 parts of an aqueous solution (solid content 10%) of polyvinyl alcohol (500-mer, saponification degree 88), 1.4 parts of a hexamethylene diisocyanate-based water-dispersed crosslinking agent (trade name "Duranate WR-70P", manufactured by Asahi Kasei Corporation, solid content 70%, NCO% = 9.2), 161.8 parts of water, and 161.8 parts of IPA were placed in a container to prepare a mixture.

[0073] The mixture prepared using a dip coater was applied to a PET film, and dried at 80°C for 1 minute and then at 150°C for 1 minute to form a coating film with a thickness of 55 nm on the PET film. The adhesion of the coating film was tested according to the description of 8.5.1 of JIS K 5400:1990, and it was found that it was hardly peeled off from the PET film. As a result, a substrate was obtained in which a highly adhesive polymer layer formed of a polymer (i) having a vinyl alcohol unit was disposed on a PET film. Then, a molded product-7 was obtained in the same manner as in Example 1 described above, except that the obtained substrate was used instead of the initiator-imparted substrate-1. The Mn of the polymer (ii) was 1.89 million, and the PDI was 1.23. The thickness of the polymer (ii) layer was measured at any 10 points ((1) to (10)) and the results are shown in Table 2.

[0074] TIFF0007626397000010.tif31170

[0075] The average thickness of the polymer (ii) layer was 1,126 nm, and the surface occupancy rate σ* was 0.24. The ratio of the minimum thickness to the average thickness of the polymer (ii) layer was 90.3%, and the ratio of the maximum thickness to the average thickness was 115%. In other words, it was found that the thickness range of the polymer (ii) layer was within the range of "-9.7 to +15.0%".

[0076] The results of infrared absorption spectrum measurement (IR chart) of the PET film and the polymer (ii) layer are shown in Figure 1. As shown in Figure 1, absorption due to polymethyl methacrylate can be confirmed in the IR chart of the polymer (ii) layer. Also, an electron microscope photograph showing the microstructure of the cross section of molded product-7 is shown in Figure 2. As shown in Figure 2, it can be seen that a polymer (ii) layer having a thickness of about 1 μm is disposed on the surface of the PET film.

[0077] (Examples 8 to 10) Molded Products-8 to -10 were obtained in the same manner as in Example 7 described above, except that the types of monomers and solvents shown in Table 3 were used and polymerization was carried out under the pressure conditions shown in Table 3.

[0078] TIFF0007626397000011.tif97170

[0079] Comparative Example 1 Comparative molded product-1 was obtained in the same manner as in Example 1, except that the polymerization was carried out under normal pressure without applying pressure. The Mn of the formed polymer (ii) was 100,000, and the PDI was 1.11. The thickness of the polymer (ii) layer was 56 nm, and the surface occupancy σ* was 0.23.

[0080] Comparative Example 2 The PET film used in Example 7 was treated with UV ozone to give hydroxyl groups to the surface of the PET film. Then, a comparative molded product-2 was obtained in the same manner as in Example 1, except that the PET film to which hydroxyl groups had been given was used instead of the PVA sheet. The Mn of the formed polymer (ii) was 2.64 million, and the PDI was 1.29. The thickness of the polymer (ii) layer was 352 nm, and the surface occupancy rate σ* was 0.05.

[0081] <Evaluation> (Rating(1)) Molded object-1, molded object-5, and comparative molded object-1 were each immersed in toluene overnight to swell the polymer (ii) layer. Thereafter, a ball indenter reciprocating sliding test was performed 1,000 times using a friction tester (trade name "Heidon friction tester type 14", manufactured by Shinto Scientific Co., Ltd.) under conditions of a load of 1,000 g, an amplitude width of 30 mm, and a sliding speed of 200 mm / min. As a result of data analysis, the friction coefficient of molded object-1 was 0.001, and there was no change in the friction coefficient even after 1,000 reciprocating movements. When the surface after the sliding test was observed with a laser microscope, no wear was observed. The friction coefficient of molded object-5 was 0.0015, and there was no change in the friction coefficient even after 1,000 reciprocating movements, but some wear marks were confirmed. In contrast, the friction coefficient of comparative molded object-1 was 0.0015 at the initial stage, but gradually increased. After 50 strokes, the coefficient of friction increased rapidly and wear marks reaching the base material were observed.

[0082] (Rating (2)) Molded object-2 was immersed in diisotridecyl adipate overnight to swell the polymer (ii) layer. Molded object-3 was immersed in water overnight to swell the polymer (ii) layer. Molded object-4 was immersed in N-(2-methoxyethyl)-N-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide (MEMPTFSI) overnight to swell the polymer (ii) layer. Thereafter, a ball indenter reciprocating sliding test was carried out in the same manner as in "Evaluation (1)" above. As a result, the friction coefficient was 0.001 in all cases, and no scraping occurred even after 1,000 reciprocations.

[0083] (Rating (3)) Molded object-7, comparative molded object-2, and molded object-6 were cut into strip-shaped test pieces. The prepared test pieces were immersed in MEMPTFSI overnight to swell the polymer (ii) layer. Instant adhesive was applied to the opposite side of the polymer (ii) layer and attached to a silicon substrate, and a ball indenter reciprocating sliding test was performed in the same manner as in the above-mentioned "Evaluation (1)". As a result, the friction coefficients of molded object-6 and molded object-7 were both 0.0007, and there was no change in the friction coefficient even after 1,000 reciprocating movements. Furthermore, no wear marks were observed. In contrast, the friction coefficient of comparative molded object-2 was 0.02, and wear marks were observed after 1,000 reciprocating movements. [Industrial Applicability]

[0084] The molded article of the present invention is useful as a material to be provided on the sliding surfaces of sliding members constituting various devices belonging to, for example, automobiles, medical devices, robots, the aerospace industry, energy, battery members, precision devices, and the like.

Claims

1. A substrate comprising a polymer (i) having vinyl alcohol units; a polymer (ii) layer provided on a surface of the substrate, the polymer (ii) including a structural unit derived from at least one monomer selected from the group consisting of an aromatic vinyl monomer, a (meth)acrylate monomer, and a (meth)acrylamide monomer; The polymer (i) and the polymer (ii) are bonded to each other through a structure represented by the following general formula (1): The number average molecular weight of the polymer (ii) is 500,000 to 5,000,000 and the molecular weight distribution (weight average molecular weight / number average molecular weight) is less than 1.5; The thickness of the polymer (ii) layer is 0.1 to 5 μm; A molded article, wherein the occupancy rate σ* of the polymer (ii) on the surface of the substrate is 0.1 or more. (In the general formula (1), R 1 represents a hydrogen atom, a methyl group, an ethyl group, a phenyl group, or an acyl group; R 2 represents a methyl group, an ethyl group, or an acyl group, "Polymer(i)" represents polymer (i), and "Polymer(ii)" represents polymer (ii).

2. The molded article according to claim 1 , wherein the layer of polymer (ii) is swollen with a solvent.

3. A method for producing the molded product according to claim 1 or 2, A step of reacting a compound represented by the following general formula (2) with a surface of a substrate containing a polymer (i) having a vinyl alcohol unit, thereby introducing a functional group represented by the following general formula (3) onto the surface of the substrate; and polymerizing at least one monomer selected from the group consisting of an aromatic vinyl monomer, a (meth)acrylate monomer, and a (meth)acrylamide monomer under a pressure condition of 10 to 1,000 MPa to form a polymer (ii), and providing a polymer (ii) layer containing the polymer (ii) on a surface of the substrate. (In the above general formula (2), R 1 represents a hydrogen atom, a methyl group, an ethyl group, a phenyl group, or an acyl group; R 2 represents a methyl group, an ethyl group, or an acyl group, X represents a chlorine atom, a bromine atom, or an iodine atom, and Y represents a chlorine atom, a bromine atom, or a hydroxyl group. (In the general formula (3), R 1 represents a hydrogen atom, a methyl group, an ethyl group, a phenyl group, or an acyl group; R 2 represents a methyl group, an ethyl group, or an acyl group, X represents a chlorine atom, a bromine atom, or an iodine atom, and "*" represents the bonding position with the polymer (i).

4. The method for producing a molded article according to claim 3, wherein the polymer (ii) is formed by surface-initiated living radical polymerization of the monomer.

5. The method for producing a molded article according to claim 3 or 4, wherein the polymer (ii) is formed by polymerizing the monomer in an ionic liquid.

6. The method for producing a molded article according to any one of claims 3 to 5, wherein the compound represented by the general formula (2) is 2-bromo-2-methylpropionic acid bromide.

7. An article comprising the molded article according to claim 1 or 2.

Citation Information

Patent Citations

  • Surface-hydrophilic polyolefin molding and method for producing the same

    JP2008133434A

  • Surface-decorated base material and polymer-coated base material

    JP2010261001A

  • Method for producing polymer

    JP2018162333A

  • Composite material

    JP2021054927A

  • Lubricant and SRT material

    WO2017171071A1